Mycosis Fungoides: A Case Report - Nyamjav, Bayartogtokh; Aleksai, Nyamdari; Yadamsuren, Enkhtur; Munkhbayar, Ariunaa (Central Asian Journal of Medical Sciences, 2020)
Objectives: Mycosis fungoides (MF) is the most common group of cutaneous T-cell lymphomas. We reported this rare diagnosed case of MF in National Dermatology Center of Mongolia. Methods: Diagnosis was based on physical examination and laboratory testing. Bioethical permission for this research was given by the Biomedical Ethics Committee of Ministry of Health in Mongolia, May 23, 2017. Results: A 78-year-old woman presented for evaluation of a 7-year history of recurrent pruritic lesions that appeared as red patches and plaques on non-sun exposed areas. She was given the initial clinical diagnosis of psoriasis. Upon examination, the morphology, histopathology and immunohistochemistry indicated MF, IB stage. Conclusions: A reliable diagnosis of mycosis fungoides might be feasible only in conjunction with clinical, histopathological, and molecular criteria.